2022
DOI: 10.1177/10711007221132284
|View full text |Cite
|
Sign up to set email alerts
|

Tibiopedal Motion Following Tendo-Achilles Lengthening or Gastrocnemius Recession in Total Ankle Replacement: A Comparative Cohort Study

Abstract: Background: End-stage ankle arthritis is a debilitating condition often necessitating total ankle replacement (TAR). Tendo-Achilles lengthening (TAL) and gastrocnemius recession (GR) are commonly performed with TAR to improve ankle dorsiflexion (DF). No studies to date have radiographically analyzed tibiopedal motion to guide surgical management. The purpose of this study is to determine the effect of a TAL or GR during TAR on radiographic tibiopedal range of motion (ROM). Methods: A retrospective review of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
(44 reference statements)
1
16
1
Order By: Relevance
“…However, most previous studies investigating ROM after TAA have looked at the effect of preoperative ROM or concomitant procedures while not specifically assessing changes to the joint level. 6,7,13,22,30 Recently, a radiographic measurement method of the joint line level in TAA was described. 18 The "joint line height ratio" (JLHR) identifies ankle-specific landmarks that remain constant following TAA.…”
Section: Introductionmentioning
confidence: 99%
“…However, most previous studies investigating ROM after TAA have looked at the effect of preoperative ROM or concomitant procedures while not specifically assessing changes to the joint level. 6,7,13,22,30 Recently, a radiographic measurement method of the joint line level in TAA was described. 18 The "joint line height ratio" (JLHR) identifies ankle-specific landmarks that remain constant following TAA.…”
Section: Introductionmentioning
confidence: 99%
“…4,22 At least 10 degrees of ankle dorsiflexion are necessary for optimal mechanics during the midstance phase of the gait cycle, 5,31 and patients undergoing TAA may therefore benefit from a concomitant triceps surae lengthening if the affected joint cannot be passively dorsiflexed to 10 degrees with the trial or real implants in place. 20,21,35…”
Section: Introductionmentioning
confidence: 99%
“…4,22 At least 10 degrees of ankle dorsiflexion are necessary for optimal mechanics during the midstance phase of the gait cycle, 5,31 and patients undergoing TAA may therefore benefit from a concomitant triceps surae lengthening if the affected joint cannot be passively dorsiflexed to 10 degrees with the trial or real implants in place. 20,21,35 The effect of concomitant triceps surae lengthening with TAA on gait mechanics has not been widely investigated. Queen et al, 35 a study that used a 1-segment foot modeling approach, found that patients who had concomitant triceps surae lengthening at the time of TAA had greater peak ankle dorsiflexion during the second rocker of the stance phase than those with TAA alone.…”
Section: Introductionmentioning
confidence: 99%
“…We read with great interest the article entitled “Tibiopedal Motion Following Tendo-Achilles Lengthening or Gastrocnemius Recession in Total Ankle Replacement: A Comparative Cohort Study” by Johnson et al 4 We truly appreciate the work for revealing an interesting phenomenon that merits further reflection, but we also wish to raise several issues that need to be addressed.…”
mentioning
confidence: 99%